ChemInform Abstract: Efficient Synthesis of Highly Enantiopure β‐Lactam Derivatives from Biocatalytic Transformations of Amides and Nitriles. Issue 46 (18th November 2014) - Ao, Yu‐Fei; Leng, Dong‐Hui; Wang, De‐Xian; Zhao, Liang; Wang, Mei‐Xiang
Abstract It is demonstrated that the amidase involved in Rh.